The Genomic Tools for Sweetpotato (GT4SP) Improvement Project - International Potato Center (2016)
The GT4SP project, launched in September 2014, is a four-year investment to develop genomic and genetic resources for sweetpotato improvement with the goal of establishing molecular marker-assisted breeding resources for the global sweetpotato breeding community